Strength training. Single versus multiple sets - Carpinelli, R. N.; Otto, R. M. (Sports Medicine, 1998)
Perhaps the most controversial element of any strength training programme is the number of sets required to increase muscular strength and hypertrophy. There is a prevalent belief that at least 3 sets of each exercise are required to elicit optimal increases in strength and hypertrophy. However, most of the studies that reported the results of training with single versus multiple sets do not substantiate this tenet. In fact, the preponderance of evidence suggests that for training durations of 4 to 25 weeks there is no significant difference in the increase in strength or hypertrophy as a result of training with single versus multiple sets. Because of the design limitations of these studies, conclusions concerning the efficacy of multiple sets should be tentative. However, there is little scientific evidence, and no theoretical physiological basis, to suggest that a greater volume of exercise elicits greater increases in strength or hypertrophy. This information may represent an important practical application of time-efficient, low-volume exercise.